El complejo de lepidopteros defoliadores de Quercus en la provincia de Cordoba - Extremera, F.M.=700 1 Cobo, A.; Perez Rodriguez, M.C.; Perez Guerrero, S.; Vargas Osuna, E.
(En, Es)
ilus., 14 ref.
Keywords: QUERCUS SUBER; QUERCUS ROTUNDIFOLIA; QUERCUS FAGINEA; LEPIDOPTERA; INSECTOS DEPREDADORES DE LAS HOJAS; ESPAÑA